Anti-inflammatory diet consumption reduced fatty liver indices - Mitra Darbandi (Nature Portfolio, 2021)
Abstract The aim of this study was to assess the association between dietary inflammatory index (DII) and non-invasive markers of liver status in adults. This cross-sectional study was performed on 8520 adults, recruited in Ravansar Non-Communicable Diseases (RaNCD) cohort study, western Iran. The DII score was calculated based on participants’ dietary intakes obtained from Food Frequency Questionnaire (FFQ). Fatty Liver Index (FLI) score was calculated by anthropometric measurements and some non-invasive markers of liver status. Linear regression models were applied to estimate the associations and adjust the possible confounding factors. A greater DII score was significantly associated with higher energy intake, body mass index (BMI), body fat mass (BFM), blood pressure, and FLI (P < 0.001). Participants with the highest DII score had a significantly higher consumption saturated fat, trans fat and red meat than those in the lowest quartile (P < 0.001). After adjustments of age and sex, participants in the highest quartile of the DII score had a greater risk of FLI (β: 0.742, 95% CI: 0.254, 0.601). More pro-inflammatory diet in participants was associated with a higher FLI. The DII score was positively associated with non-invasive liver markers. Thus, having an anti-inflammatory diet can help balance liver enzymes, reduce obesity, and decrease fatty liver.